Uncertainty, intangible capital, and productivity dynamics - Edoardo Palombo (Queen Mary University of London, School of Economics and Finance, 2020)
Following an unparalleled rise in uncertainty over the Great Recession, the US economy has been experiencing anaemic productivity growth. This paper offers a quantitative study on the link between uncertainty and low productivity growth. Firstly, using micro level data I show that uncertainty accounts for half of the drop in intangible capital stock during the Great Recession. Secondly, to investigate the effect of uncertainty on productivity growth dynamics, I present a novel general equilibrium endogenous growth model with heterogeneous firms that undertake intangible capital investment subject to non-convex costs and time-varying uncertainty. I show that uncertainty can generate slow recoveries and a persistent slowdown in productivity growth when accounting for the empirical discrepancy between the realised and expected changes to the second-moment of fundamentals.
Keywords: O40; O41; O51; 330; Uncertainty; R&D; Innovation; Productivity; Great Recession; Intangible Capital; Slow Recoveries